DEVELOPING SELF-DEVELOPMENT SKILLS IN STUDENTS (Web of Teachers: Inderscience Research, 2024)
The article examines the importance of developing students' skills for independent development as a crucial aspect of the modern educational system. The historical evolution of this concept is analyzed, alongside domestic and international approaches and their impact on educational outcomes. Attention is paid to the methods and practices that foster independence and the challenges associated with implementing them in the learning process.